PENGARUH PELATIHAN PLAIOMETRIC SIDE JUMP SPRINT TERHADAP KECEPATAN DAN KEKUATAN OTOT TUNGKAI - Mastikayasa, I Kadek (Universitas Pendidikan Ganesha, 2013)
This research refer to improve the influence of training plaiometric side jump sprint to speed and strength of muscle. This Research is sham experiment with the device of research of the non randomized control group pretest posttest design. This Subjek Research is extracurricular participant student football of SMA N 1 Abiansemal on years leader 2012 / 2013 counted 42 people later;then divided to become 2 group. Speed measured by tes run with quickly 60 metre, while strength of muscle measured with the instrument of tes leg dynamometer, hereinafter data analysed by uji-t independent of level signifikansi 0,05 constructively program SPSS 16,0. Result of analysis obtained by training of plaiometric of side jump sprint have an effect on to make of speed ( p<0,000). And Training of plaiometric side jump sprint have an effect on to make of strength of muscle ( p<0,000). That: ( 1) training of plaiometric side jump sprint have an effect on to improve the speed at extracurricular participant student football of SMA N 1 Abiansemal on years leader 2012 / 2013 and ( 2) training of plaiometric side jump sprint have an effect on to improve the strength of muscle at extracurricular participant student football of SMA N 1 Abiansemal on years leadre 2012 / 2013. Suggested to athletic perpetrator ( builder, coach, athletic teacher and atlet) by using training of plaiometric side jump sprint as one of the alternative in improving speed and strength of muscle.